Synthetic photometry of OB star clusters with stochastically sampled IMFs: analysis of models and HST observations - Orozco-Duarte, Rogelio; Wofford, Aida; Vidal-García, Alba; Bruzual, Gustavo; Charlot, Stephane; Krumholz, Mark R.; Hannon, Stephen; Lee, Janice; Wofford, Timothy; Fumagalli, Michele; Dale, Daniel; Messa, Matteo; et al. (Monthly notices of the Royal Astronomical Society, 2021)
We present a pilot library of synthetic NUV, U, B, V, and I photometry of star clusters with stochastically sampled IMFs and ionized gas for initial masses, Mi = 103, 104, and 105 M⊙; t = 1, 3, 4, and 8 Myr; Z = 0.014 and Z = 0.002; and log(US) = −2 and −3. We compare the library with predictions from deterministic models and observations of isolated low-mass (<104 M⊙) star clusters with co-spatial compact H ii regions. The clusters are located in NGC 7793, one of the nearest galaxies observed as part of the HST LEGUS and Hα-LEGUS surveys. (1) For model magnitudes that only account for the stars: (a) the residual |deterministic mag - median stochastic mag| can be ≥0.5 mag, even for Mi = 105 M⊙; and (b) the largest spread in stochastic magnitudes occurs when Wolf-Rayet stars are present. (2) For Mi = 105 M⊙: (a) the median stochastic mag with gas can be >1.0 mag more luminous than the median stochastic magnitude without gas; and (b) nebular emission lines can contribute with $\gt 50{{\ \rm per\ cent}}$ and $\gt 30{{\ \rm per\ cent}}$ to the total emission in the V and I bands, respectively. (3) Age-dating OB-star clusters via deterministic tracks in the U-B versus V-I plane is highly uncertain at Z = 0.014 for Mi ∼ 103 M⊙ and Z = 0.002 for Mi ∼ 103-105 M⊙. (4) For low-mass clusters, the V-band extinction derived with stochastic models significantly depends on the value of log(US). (5) The youngest clusters tend to have higher extinction. (6) The majority of clusters have multi-peaked age PDFs. (7) Finally, we discuss the importance of characterizing the true variance in the number of stars per mass bin in nature.